Precious metal recovery from waste printed circuit boards using cyanide and non-cyanide lixiviants – A review. (November 2015) - Akcil, Ata; Erust, Ceren; Gahan, Chandra Sekhar; Ozgun, Mehmet; Sahin, Merve; Tuncuk, Aysenur
Highlights: Assess cyanide and non-cyanide leaching of precious metals from PCBs. Compare new lixiviants for precious metal recovery with conventional hydroprocesses. Analysis of cyanidation together with thiourea and thiosulphate leaching of E-waste. Emphasise economic and environmental issues for cyanide and non-cyanide leaching. Future directions and feasibility to develop precious metal leaching from E-waste. Abstract: Waste generated by the electrical and electronic devices is huge concern worldwide. With decreasing life cycle of most electronic devices and unavailability of the suitable recycling technologies it is expected to have huge electronic and electrical wastes to be generated in the coming years. The environmental threats caused by the disposal and incineration of electronic waste starting from the atmosphere to the aquatic and terrestrial living system have raised high alerts and concerns on the gases produced (dioxins, furans, polybrominated organic pollutants, and polycyclic aromatic hydrocarbons) by thermal treatments and can cause serious health problems if the flue gas cleaning systems are not developed and implemented. Apart from that there can be also dissolution of heavy metals released to the ground water from the landfill sites. As all these electronic and electrical waste do posses richness in the metal values it would be worth recovering the metal content and protect the environmental from the pollution. Cyanide leaching has been a successful technology worldwide for the recovery of precious metals (especially Au and Ag) from ores/concentrates/waste materials. Nevertheless, cyanide is always preferred over others because of its potential to deliver high recovery with a cheaper cost. Cyanidation process also increases the additional work of effluent treatment prior to disposal. Several non-cyanide leaching processes have been developed considering toxic nature and handling problems of cyanide with non-toxic lixiviants such as thiourea, thiosulphate, aqua regia and iodine. Therefore, several recycling technologies have been developed using cyanide or non-cyanide leaching methods to recover precious and valuable metals.